Fucoxanthin Extracted from the Microalgae Phaeodactylum tricornutum Ameliorates Alzheimer’s Pathologies with the Reduction of Aβ-Induced NLRP3 Inflammasome Activation in APP/PS1 Mice - Ahn, Na-Hyun; Hong, Sung-Chul; Hong, Chi Rac; Lee, Eun Ha; Lee, Joo-Hee; Choi, Su-Bin; Jung, Jaewoon; Kim, Yebeen; Kim, Jung-Seok; Park, Keunwan; Kim, Yun Kyung; Kim, Youngsoo; et al. (Springer Nature, 2026)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder, one of the most common types of dementia, accompanying severe learning and memory dysfunctions. In AD brains, the misfolded aggregation and deposits of amyloid-β (Aβ) and tau are frequently observed before the cognitive symptom onset; thus, trials for alleviation of these lesions are considered commensurate strategies with AD treatment. Additionally, increasing evidence suggests that misfolded and aggregated proteins induce the activation of microglia and astrocytes by the release of the inflammatory mediators via the activation of the inflammatory signaling cascade, which consequently contributes to AD pathogenesis. Here, we investigated the therapeutic potential of fucoxanthin, a compound derived from the microalgae Phaeodactylum tricornutum, in mitigating AD pathologies. Fucoxanthin was shown to inhibit the aggregation of Aβ and tau, converting their aggregates to monomeric forms. In the brain of APP/PS1 transgenic mice, fucoxanthin administration significantly reduced the levels of Aβ plaques and hyperphosphorylated tau and further ameliorated cognitive impairments by inhibiting the activation of microglia and astrocytes. Notably, fucoxanthin effectively regulated Aβ-induced NLRP3 inflammasome activation in astrocytes, reducing neuroinflammation associated with AD. Thus, our findings showing the multifaceted therapeutic mode of action of fucoxanthin against AD provide that fucoxanthin would have promising roles in the strategies of AD treatment.